Learning to make a difference: Christian Aid Ireland’s adaptive progra mme management in governance, gender, peace building and human rights - Booth, David; Balfe, Karol; Gallagher, Róisín; Kilcullen, Gráinne; O'Boyle, Sarah; Tiernan, Alix (ODI, 2018)
This paper assesses the relevance of adaptive or trial-and-error appro aches to the field of governance, peace building and human rights. Tac kling the problems of poverty, vulnerability and exclusion that persis t in parts of the world that continue to be affected by violence or po litical insecurity is difficult for several reasons. For one, because of the complexity of the prevailing social, economic and political sys tems, solutions to chronic problems are far from obvious. One response to this aspect of the challenge is adaptive programme design and mana gement. This paper is the product of a multi-year collaboration betwee n ODI and the core team of Christian Aid Ireland to assess the relevan ce of adaptive or trial-and-error approaches to the field of governanc e, peace building and human rights. It explains the basis on which Chr istian Aid Ireland’s current five-year programme has become committed to an adaptive approach. It then describes and seeks to draw lessons f rom the programme’s first year of experience, considering the possible implications for implementation over the coming years. The authors fi nd that to get full benefits from the move to adaptive management, the new ways of working and their underlying principles will need to beco me more embedded in organisational practices and cultures.